Antibacterial properties of linolenic sophorolipid and its chemically esterified methyl ester form - Reetika, Gupta; Kumar, Uma S.; Asmita, Prabhune (Research Journal of Biotechnology, 2012)
The antibacterial activity of Linolenic SL mixture (containing 80% lactone) and its methyl ester derivative against Gram positive (B. subtilis) and Gram negative (E. coli and P. aeruginosa) bacteria is reported here. Bacterial cultures were treated with increasing concentrations of Linolenic SL mixture and its methyl ester derivative and antibacterial activity was checked at different time-intervals (2, 4 and 6 hrs) using standard dilution micromethod and spread plate method. Decrease in bacterial colonies was observed with increase in concentrations of compounds as well as incubation time but the level of effectiveness varies with the compound and bacteria. The minimum inhibitory concentrations (MIC) of Linolenic SL mixture (LNNSL, containing 80% lactone) against B. subtilis, E. coli and P. aeruginosa were found to be 20, 10 and 10 mu g ml(-1) respectively. The MIC values of methyl ester form (LNNSLME) against B. subtilis, E. coli and P. aeruginosa were determined to be >20, 20 and 20 mu g ml(-1) respectively. The results suggest that Linolenic SL mixture (containing 80% lactone) as compared to its methyl ester derivative showed good antibacterial activity towards both the Gram positive and Gram negative bacteria and were found to be more potent against Gram negative bacteria.
Keywords: antibacterial activity; Bacillus subtilis; Escherichia coli; Linolenic sophorolipid mixture; Minimum inhibitory concentration; Pseudomonas aeruginosa; Sophorolipid methyl ester